Effectiveness of a Simplified ESP Curriculum for Adult Learners - Khalid A. Alghamdi (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This research investigates the effectiveness of a simplified English for Specific Purposes (ESP) curriculum tailored for male learners aged 35-55. The study employed a mixed-methods approach, combining quantitative proficiency assessments with qualitative insights from interviews and classroom observations. Sixty participants engaged in a 12-week program that focused on essential grammar, vocabulary building, and interactive tasks aligned with their professional needs. The curriculum was designed to address the specific linguistic and communicative demands of workplace scenarios, ensuring immediate applicability of the skills learned. The results indicate significant improvements in speaking, listening, and reading skills, with mean scores increasing by (30%), (24.1%), and (25.9%), respectively. Participants reported enhanced confidence in using English in professional settings, attributing this improvement to the curriculum's practical focus and opportunities for real-time practice during interactive tasks. Qualitative data from interviews revealed that learners found the curriculum highly relevant to their workplace needs, with many participants applying newly acquired vocabulary and expressions directly in their jobs. The study highlights the potential of minimalist curriculum design in adult ESP education, demonstrating that streamlined, context-specific approaches can effectively address the unique challenges faced by adult learners. By focusing on essential language skills and reducing cognitive load, the simplified curriculum not only improved language proficiency but also boosted learner motivation and engagement. These findings have important implications for ESP educators and curriculum designers, suggesting that simplified, goal-oriented programs can yield superior outcomes for adult learners.